The Relevance of The Book of Ta'liim Al-Muta'allim in Character Building in The Era of Industrial Revolution 4.0 - Firdaus Firdaus; Hermawan Hermawan (AMIN: International Journal of Islamic Education and Knowledge Integration, 2023)
In the current era of the industrial revolution 4.0, education in Indonesia is gradually losing its spiritual essence. Technological advances provide opportunities for everyone to access unlimited information. The positive and negative impacts of these advances have direct consequences in various fields, including character education. Kitab Ta'lim Muta'allim by al-Zarnuji is a classic book that contains values that have relevance to the character of national education applied in educational institutions in Indonesia. This type of research is library research using descriptive methods and data analysis (content analysis). The educational character values contained in Ta'lim Muta'allim include: the value of intention, deliberation, patience and steadfastness, respect and khidmah, istiqamah, self-sacrifice, lofty ideals, hard work, tawakkal, mutual advice, taking lessons, the value of wara'. These values are still relevant to the 17 values of character education according to the Ministry of National Education.